Validation of energy conservation behaviour for Malaysia university students using exploratory and confirmatory factor analysis - Hassan, Noor Asiah; Dajvinder Singh; Mohd Hassan, Rodiah (EDUCATUM Journal of Social Sciences, 2024)
Given the increasing urgency of addressing global environmental challenges, research on energy conservation in educational settings is critical. University students represent a significant demographic with the potential to drive behavioural change and promote sustainable practices. By understanding and influencing their energy conservation behaviours, this research contributes to the broader efforts to mitigate environmental impact and foster a culture of sustainability. This study aims to validate the Environment Conservation Behavioural Survey (ECOBS), an instrument designed to assess university students' behaviours and intentions regarding energy conservation, through the lens of the Theory of Planned Behaviour (TPB). The ECOBS model integrates five key variables: behaviour, intention, perceived behavioural control, environmental education, and attitude. Initially, a pilot study with 150 respondents was conducted, followed by Exploratory Factor Analysis (EFA) using SPSS. Subsequently, primary data were collected from 400 respondents and analysed using Confirmatory Factor Analysis (CFA) in AMOS. The findings confirm that the ECOBS instrument meets the stringent criteria for convergent, construct, and discriminant validity, as well as reliability, demonstrating its robustness in evaluating students' intentions and behaviours towards energy conservation. The validated ECOBS instrument not only identifies key predictors of energy conservation behaviours but also offers practical insights for stakeholders aiming to enhance such behaviours among students. The rigorous validation process underscores the ECOBS instrument's value as a reliable and valid tool for measuring and promoting energy conservation behaviours in educational settings. This instrument can serve as a foundation for future studies, contributing to the development of targeted interventions that foster sustainable behaviours among university students.